Myocarditis associated with malarial fever: An unusual presentation - Anoop Kumar; Prachi Garg; Jai Prakash; Gaurav Arya; Kirti Berwal; Ekal Arora (Asian Journal of Medical Sciences, 2022)
Malaria is endemic in India and complicated malaria is usually caused by Plasmodium (P) falciparum, but Plasmodium vivax can also cause life-threatening conditions in some cases. We report one such case of 47 years male presenting with myocarditis associated with P. vivax malaria.